ZrB2-MoSi2 ceramics: A comprehensive overview of microstructure and properties relationships. Part I: Processing and microstructure. Issue 6 (June 2019) - Grohsmeyer, Ryan J.; Silvestroni, Laura; Hilmas, Gregory E.; Monteverde, Frédéric; Fahrenholtz, William G.; D'Angió, Andrea; Sciti, Diletta
Abstract: This study systematically correlates processing with quantitative microstructural information over an extended compositional range for ZrB2 -MoSi2 ceramics, with MoSi2 contents ranging from 5 to 70 vol% and diboride starting particle sizes ranging from 3 to 12 μm. Fifteen different ceramics were hot pressed between 1750 and 1925 °C. Plastic deformation of MoSi2 contributed to initial densification, but some of the MoSi2 decomposed during the later stages of hot pressing. Finer diboride particles required lower temperatures to densify (1750 to 1850 °C) compared to coarser diboride particles (1900 °C). Increasing MoSi2 content led to a decrease in sintering temperature. As MoSi2 content increased, ZrB2 grain size decreased and MoSi2 cluster size increased. Starting powders with lower impurity contents and isothermal vacuum holds contributed to lower oxide impurity contents in the final ceramics. A diboride core-shell microstructure involving (Zr1-x, Mox )B2 solid solutions formed in all compositions with Mo contents in the solid solution shells ranging from 3 to 6 at%. This work identified specific relationships between starting composition, processing conditions and final microstructure, showing how microstructure and properties could be tailored by processing. The outcomes of this extensive study will serve as guidelines for the design of other structural ceramics that have to attain determinate thermo-mechanical properties for targeted applications.